The non-western challenger? The rise of a Sino-centric China - Andreas Bøje Forsby (Danish Institute for International Studies (DIIS), 2011)
What are the implications of China's rapid rise for international order? This report seeks to answer the question from an identity perspective. The key argument is that China is currently undergoing an identity shift towards Sino-centrism, that is, a self-centering tendency to turn narrative attention towards the internally generated, specifically Chinese hallmarks associated with China's civilizational past and cultural heritage. The bulk of the report analyzes the four identity markers of Sino-centrism: Sino-civilization, Confucian philosophy, dynastic authoritarianism, and Han-ethnocentrism. It is argued that these identity markers provide China with a distinct, non-Western, societal template that may potentially set a new course for Chinese foreign policy. Finally, the report discusses the likely characteristics of a Sino-centric foreign policy and suggests how it may bring China in conflict with several aspects of the current international order as well as the United States itself.
Keywords: 300